Emotion mapping: Exploring creative methods to understand the psychology of long-term injury. Issue 1 (March 2022) - Goldman, Aura; Gervis, Misia; Griffiths, Michael
This methodological study details the effectiveness of emotion mapping as a method to explore the lived experiences of professional male athletes ( n = 9) with a long-term injury. This represents the first use of emotion mapping to garner phenomenal knowledge on long-term injury within a sport psychology context, and as such is a departure from traditional approaches in this field. Following an orientation meeting, each participant was asked to produce an emotion map in the privacy of their home of two critical spaces occupied during their rehabilitation. Using video conferencing software, they were then asked to narrate their map, to facilitate understanding of their lived experiences of injury. Overall, the method was found to be efficacious in supporting existing literature on injury and revealing previously unknown aspects of long-term injury. In particular, the study provided phenomenal knowledge that was previously absent. As such, recommendations are made for the use of emotion mapping both as an effective research technique, and as a therapeutic tool.